Exploring the contribution of mechano-sensing to cardiomyopathy. (10th June 2022) - Azad, A; Jiang, H; Hooper, C; Davies, B; Watkin, H; Gehmlich, K
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Medical Research Council (MR/V009540/1), Wellcome Trust (201543/B/16/Z) British Heart Foundation (FS/12/40/29712). Hypertrophic cardiomyopathy (HCM) is an inherited cardiac condition associated with diastolic dysfunction and sudden cardiac death. Disease genes for HCM are traditionally coding for proteins involved in force generation. More recently, it has emerged that variants in genes coding for proteins involved in biomechanical stress-signalling can also cause HCM. One such protein is filamin C, with proposed mechano-sensing functions in the heart. Within the protein, the immunoglobulin-like domain 20 (Ig20) may play a crucial role in mediating binding to muscle specific ligands. While the mechano-sensing functions of filamin C have been investigated well in skeletal muscle, the underlying cardiac disease mechanisms are not completely understood. Aim: This work attempts to provide insights into the role of filamin C in cardiac mechano-sensing and dissect disease pathways leading to HCM in the presence of the FLNC variants in Ig20. Methods: Using mass spectrometry, we aimed to provide a detailed analysis of the proteome of mice carrying the filamin C variant, using ventricular tissue samples from 14wk old homozygous mice. Samples were subject to molecular biology technical and underwent subcellular fractionation (n = 6 per genotype) and were investigated by label-free mass spectrometry. Results: Utilising whole genome sequencing, a heterozygous FLNC missense variant in Ig20 was identified in a three-generation family affected by HCM. Mice carrying this variant recapitulate molecular features of HCM in the homozygous setting. Three proteins (FLNC, MYH7, MYOT) were found to be upregulated in the myofilament-enriched fraction. Up-regulations of key proteins were found to relocalise towards load-baring sites. Conclusion: Our data indicate that changes in filamin C and its binding partners expression and localisation are involved in the pathogenesis of HCM in this mouse model.